Assessment of Islamic Education Subjects in the Merdeka Curriculum at SMA N 3 Sampit - Kurniawan, Kurniawan; Supriadi, Gito; Mahmudah, Istiyati (Lembaga Yasin AlSys, 2025)
The Independent Curriculum (Kurikulum Merdeka) introduces a new educational paradigm in Indonesia that emphasizes learner autonomy and student-centered approaches. This study investigates the implementation of Islamic Education (PAI) assessments under the Independent Curriculum at SMA Negeri 3 Sampit, focusing on the processes of planning, implementation, and evaluation. A qualitative case study design was employed, with data collected through observations, in-depth interviews with key stakeholders, and document analysis. Data validation was conducted using source and technique triangulation. The findings reveal that PAI assessment implementation comprises three core stages: planning, which includes the preparation of the School Operational Curriculum (KOSP) and thematic teaching modules; implementation, which integrates both intracurricular learning and Proyek Penguatan Profil Pelajar Pancasila (P5); and evaluation, which includes formative and summative assessments. Formative assessments are conducted through observation, portfolios, and project-based evaluations, while summative assessments utilize tools such as case study-based tests to measure final student competencies. The main challenges identified include limited teacher readiness, adherence to conventional assessment mindsets, and insufficient understanding of holistic evaluation practices. Despite these challenges, the school demonstrates adaptive strategies by developing assessment rubrics that integrate cognitive, spiritual, and social domains. These efforts reflect a broader institutional commitment to the core principles of the Independent Curriculum and the advancement of authentic, student-centered Islamic education.